The Effect of the Five-Year Learning Cycle Strategy on Developing Artistic Expression among Elementary School Students in Art Education (Al-Academy, 2026)
This research aims to explore the impact of using the five-step learning cycle strategy on developing artistic expression skills among primary school students in art education. The researcher adopted an experimental approach based on designing two equivalent groups (experimental and control) with the application of pre- and post-skill tests, consistent with the nature of the objectives and hypotheses presented. The experiment was implemented on a sample of (60) male and female students from the fifth grade of primary school at Busra Mixed Primary School/Al-Karkh II (morning study). The sample was distributed equally between the two groups. The study used a skill test tool developed according to objective criteria to measure the development of artistic expression skills. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) to arrive at accurate and reliable results. The results of the study showed the following:Students in the experimental group who learned according to the five-step learning cycle strategy significantly outperformed students in the control group who learned using the traditional method, in terms of artistic performance, self-confidence, and responsibility.The strategy contributed to developing students' expressive abilities and enabled them to produce innovative artistic ideas consistent with the lesson content